2022
DOI: 10.1007/s00198-021-06218-5
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of the associations between bone health and three different intensities of accelerometer-derived habitual physical activity in children and adolescents: a systematic review

Abstract: Positive associations have been identified between bone outcomes and accelerometer-derived moderate (MPA) and vigorous (VPA) physical activity (PA) in youth; however, it remains unclear which intensity is most beneficial. This systematic review aimed to summarise accelerometer-derived methods used to estimate habitual PA in children and adolescents and determine whether the magnitude of association was consistently stronger for a particular intensity (MPA/MVPA/VPA). Observational studies assessing associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
(396 reference statements)
0
2
0
Order By: Relevance
“…The beneficial intensity of >700 mg identified in the present study is equivalent to the VPA threshold identified in calibration studies using wrist-worn raw accelerometry in children (Hildebrand et al, 2014;Phillips et al, 2013). Several previous cross-sectional studies have also reported that accelerometer-derived VPA is most strongly associated with bone outcomes in comparison to other predefined PA intensities (e.g., MPA and MVPA) (Brailey et al, 2022).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The beneficial intensity of >700 mg identified in the present study is equivalent to the VPA threshold identified in calibration studies using wrist-worn raw accelerometry in children (Hildebrand et al, 2014;Phillips et al, 2013). Several previous cross-sectional studies have also reported that accelerometer-derived VPA is most strongly associated with bone outcomes in comparison to other predefined PA intensities (e.g., MPA and MVPA) (Brailey et al, 2022).…”
Section: Discussionsupporting
confidence: 69%
“…[MPA] and vigorous PA [VPA]), using cut-points (numerous) that are selected at the outset (Brailey et al, 2022). As a result, the short bursts of high-intensity activity that are required to initiate osteogenesis (Turner et al, 2003) and sporadically performed by children (Bailey et al, 1995;Baquet et al, 2007) are "over-smoothed" and misclassified as lower intensity activity (Nilsson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence has already established that increased amounts and higher intensity levels of physical activity (PA) in children and adolescents are associated with many beneficial health outcomes [ 1 ]. For instance, PA was found to be positively associated with bone health [ 2 4 ], cardiorespiratory fitness [ 5 , 6 ], brain activation and microstructural plasticity [ 7 ], self-rated health [ 8 ], well-being and quality of life [ 9 ], and negatively associated to adiposity and cardiometabolic risk score [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported that taking more steps per day was associated with lower mortality risk, where the risk plateaued at approximately 6,000–8,000 steps or 8,000–10,000 steps per day for older (≥60 years) or younger adults (<60 years), respectively (Paluch et al, 2022). Most of the previous research on physical activity has concentrated on how the total amount of activity based on its intensity and duration is linked to health (Amagasa et al, 2018; Brailey et al, 2022; Lu et al, 2022). However, analyzing only the total amount of physical activity might overlook a complete understanding of the activity behavior since the metrics of the total amount of physical activity tends to exclude or underestimate the effect of temporal variations of physical activity.…”
Section: Introductionmentioning
confidence: 99%